Characteristic dynamics of height and weight in preschool boys with constitutional delay of growth and puberty or hypogonadotropic hypogonadism. (26th June 2019) - Reinehr, Thomas; Hoffmann, Elisa; Rothermel, Juliane; Lehrian, Theresa Johanna; Binder, Gerhard
Abstract: Objective: Constitutional delay of growth and puberty (CDGP) is a frequent variant of the normal leading to short stature and/or pubertal delay. To distinguish CDGP from hypogonadotropic hypogonadism (HH), we evaluated height, growth and weight pattern of CDGP and HH in the first 5 years of life. Design and patients: We studied retrospectively height and weight in the first 5 years (y) of life in 54 boys with CDGP and 8 boys with HH. Results: In boys with CDGP, height‐SDS decreased (change −0.94 (interquartile range [IQR] −1.69 to −0.05); P  < 0.001) between birth and 2 years. BMI‐SDS decreased (change −0.38 (IQR −1.21‐0.16); P  < 0.001) in the same time period. There were no significant changes in height‐SDS or BMI‐SDS between 2 years and 5 years, while height‐SDS (change + 1.49 (IQR 1.02‐1.95); P  < 0.001) and BMI‐SDS (change + 0.91 (IQR 0.12‐1.69); P  < 0.001) increased between pubertal and adult age. In boys with HH, height‐SDS and BMI‐SDS did not change significantly in the first 5 years of life. Height‐SDS decreased (change −1.39 (IQR −1.96 to −0.67); P  = 0.018) significantly between 5 years of life and puberty, while there were no significant changes in BMI‐SDS in this time period. At pubertal age, BMI‐SDS was significantly ( P  = 0.001) higher in boys with HH compared with boys with CDGP. Conclusion: Height deflection and weight deflection in CDGP occur already during the first two years of life in contrast to HH. This different pattern of growth and weight might be helpful to distinguish CDGP from HH.